Home » Blog » Establish the given formulas for some given sums

Establish the given formulas for some given sums

  1. Assume that

        \[ \sum_{n=0}^{\infty} \frac{x^n}{n!} = e^x \qquad \text{for all } \ \ x. \]

    Show that

        \[ \sum_{n=1}^{\infty} \frac{n^2 x^n}{n!} = (x^2 + x)e^x, \]

    assuming that we can operate on infinite sums in the same way we can operate on finite sums.

  2. Given that

        \[ \sum_{n=1}^{\infty} \frac{n^3}{n!} = ke \]

    for a positive integer k. Find the value of k, without attempting to justify the formal manipulations of the infinite series.


  1. We compute,

        \begin{align*}  &&\sum_{n=0}^{\infty} \frac{x^n}{n!} &= e^x \\[9pt]  \implies && \sum_{n=0}^{\infty} \frac{nx^{n-1}}{n!} &= e^x &(\text{differentiating})\\[9pt]  \implies && \sum_{n=0}^{\infty} \frac{nx^n}{n!} &= xe^x &(\text{multiplying by }x)\\[9pt]  \implies && \sum_{n=0}^{\infty} \frac{n^2 x^{n-1}}{n!} &= e^x (x+1) &(\text{differentiating})\\[9pt]  \implies && \sum_{n=0}^{\infty} \frac{n^2 x^n}{n!} &= e^x (x^2+x) &(\text{multiplying by }x). \end{align*}

  2. Starting with the formula in part (a) (and noting that since the n =0 term is zero we can run the sum from n=1 to infinity) we have

        \begin{align*}  && \sum_{n=1}^{\infty} \frac{n^2 x^n}{n!} &= e^x (x^2  + x) \\[9pt]  \implies && \sum_{n=1}^{\infty} \frac{n^3 x^{n-1}}{n!} &= e^x (x^2 + 3x + 1) \\[9pt]  \implies && \sum_{n=1}^{\infty} \frac{n^3}{n!} &= 5e &(\text{letting }x =1) \\[9pt]  \implies && k &= 5. \end{align*}

Point out an error, ask a question, offer an alternative solution (to use Latex type [latexpage] at the top of your comment):